Clinical diagnosis and treatment outcomes for parapharyngeal space schwannomas: A single‐institution review of 21 cases. Issue 3 (21st November 2017) - Sato, Yoichiro; Imanishi, Yorihisa; Tomita, Toshiki; Ozawa, Hiroyuki; Sakamoto, Koji; Fujii, Ryoichi; Shigetomi, Seiji; Habu, Noboru; Otsuka, Kuninori; Watanabe, Yoshihiro; Sekimizu, Mariko; Ogawa, Kaoru
Abstract: Background: Because the incidence of schwannoma arising from the parapharyngeal space (PPS) is very low, no studies have analyzed extirpation methods and postoperative neurological complications exclusively in PPS schwannomas. Methods: The preoperative diagnosis and clinical outcomes of surgical treatment in 21 patients with PPS schwannoma who underwent surgery were investigated. Results: Neurological deficit of the involved nerve developed in all patients regardless of the extirpation method used. However, the incidence of first bite syndrome in sympathetic chain schwannoma was significantly lower after intracapsular enucleation (40%) than after total resection (100%; P = .045). Furthermore, the incidence of postoperative complications unrelated to the involved nerve was lower after intracapsular enucleation (0%) than after total resection (42.9%; P = .055). Conclusion: Although postoperative neurological deficit of the involved nerve was unavoidable in PPS schwannoma, intracapsular enucleation could be beneficial by reducing its severity and the incidence of complications unrelated to the involved nerve.